THE USE OF LEARNING JOURNAL ASSESSMENT IN DISCOVERING STUDENTS’ PROBLEM IN WRITING RECOUNT TEXT - Harumsari, Dewi; ., Sofian; Susilawati, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research aims to find out students’ writing performance in recount text that could be assessed through learning journal. Besides, it also aims to find out students’ problem in writing recount text and also the causes of the problem. This research was qualitative research. The sample was 30 Grade X students of SMAN 2 Pontianak in academic year 2014/2015.The techniques of data collecting were observation, test, and interview. The result shows that the average percentage of students’ performance in writing recount text that could be assessed through learning journal was 74,16% which classified into good category. In addition, the result of the research also shows that the most problem in writing recount text that could be discovered through learning journal was vocabulary mastery the most causes of problem was students’ understanding about English language in terms of sentence structure, vocabulary, and also text organization of recount text. Key words:Learning Journal, Recount Text Writing Abstrak: Penelitian ini bertujuan untuk mengetahui hasil penulisan teks recount siswa yang dapat dinilai menggunakan jurnal belajar. Selain itu, penelitian ini juga bertujuan untuk mengetahui masalah dan penyebab dari masalah dalam menulis teks recount yang dapat diungkap melalui penulisan jurnal belajar. Penelitian ini adalah sebuah penelitian kualitatif. Sampel dalam penelitian ini adalah 30 siswa kelas X di SMAN 2 Pontianak pada tahun akademik 2014/2015. Teknik pengumpul data yang digunakan adalah observasi, tes, dan wawancara. Hasil penelitian ini menunjukan bahwa persentase rata-rata dari hasil penulisan recount text siswa adalah 74,16 % yang termasuk dalam kategori baik. Selain itu, hasil penelitian ini juga menunjukkan bahwa masalah utama yang dihadapi siswa dalam menulis teks recount adalah penguasaan perbendaharaan kata dalam bahasa Inggris dan penyebab utamanya adalah ketidakpahaman siswa tentang penggunaan bahasa Inggris baik dari struktur bahasa, penguasaan perbendaharaan kata, dan juga struktur teks recount. Kata kunci: Jurnal Belajar, Menulis Teks Recount